Synthesis and Crystal Structure of 1-(1H-Benzotriazol-1-yl)-2-(2-chlorophenyl)-2-oxoethyl Benzoate - Qu, Bin; Sun, Jie; Zhu, Yingjie; Li, Fang (Asian Journal of Chemistry, 2010)
The crystal structure of 1-(1H-benzotriazol-1-yl)-2-(2-chlorophenyl)- 2-oxoethyl benzoate has been determined by single crystal X-ray diffraction method. The crystal belongs to orthorhombic system, space group P212121 with unit cell constants a = 15.186(4), b = 1.896(2), c = 11.819(3) Å, V = 1955.6(7) Å3, Z = 4, Dc = 1.378 g/cm3, μ = 0.224 mm-1, F(000) = 840, R and wR are 0.0479 and 0.1251, respectively for 3451 unique reflections with 2911 observed reflections [I > 2σ(I)]. The crystal packing is stabilized by π-π interactions and van der Waals forces.